Evaluation of Web Search Engines: A Comparative Study - Ketheeswaren, S.; Rosaline Mary, S.; Visvanath, B. (Kumaraguru College of Technology, 2008)
Three Web search engines, namely, Alta Vista, Excite, and Lycos, were compared and evaluated in terms of their search capabilities (e.g., Boolean logic, truncation, field search, word and phrase search) and retrieval performances (i.e.. precision and response time) using sample queries drawn from themes of the conference: Re-Building the Libraries. Recall, the other evaluation criterion of information retrieval. is deliberately omitted from this study because it is impossible to assume how many relevant items there are for a particular query in the huge and ever changing Web system. We found that Alta Vista outperformed Excite and Lycos in both search facilities and retrieval performance although Lycos had the largest coverage of Web resources among the three Web search engines examined.
Keywords: Search Engines; Precision; Information Retrievals